(untitled) (Dhaka University Journal of Science, 2024)
Laddus are very popular sweets all over the South Asian countries including Bangladesh. Commercially accessible sweets (Laddus) contain a variety of Yellow 5 and Yellow 6 dyes, which are hazardous when consumed in excess. In this study, the amount of Yellow 5 and Yellow 6 in twenty-five Yellow-colored Laddus from various sweet shops in Dhaka, Bangladesh, was determined using a UV-visible spectrophotometer at 425 and 482 nm, respectively. Quantification was done using external calibration curves of the standard Yellow 5 and Yellow 6 and the calibration curves showed excellent linear correlation co-efficient (R2) of 0.999 and 0.998 for them, respectively. Of the twenty-five samples, eleven had Yellow 5 in the range of 0.915-6.790 mgkg-1, and eight had Yellow 6 in the range of 0.223-4.315 mgkg-1. The rest of the samples did not contain any Yellow 6 as well as Yellow 5. Dhaka Univ. J. Sci. 72(2): 45-51, 2024 (July)